Effectivity Of Zeolite As An Adsorbent For Methyl Violet Adsorption - Wardalia, Wardalia; Septi, Dede; Dewiyanti, Isna; Kanani, Nufus; Adiwibowo, Muhammad Triyogo (World Chemical Engineering Journal, 2023)
The textile industry in Indonesia is developing. This development aligns with the amount of waste produced, such as dyes and metal waste, which can harm the environment and must be processed. One of the waste treatment methods that can be used is adsorption using zeolite. This study aims to determine the absorption effectiveness of Bayah natural zeolite adsorbents on lead and methyl violet waste. The zeolite was mashed and uniformed in size up to 80 mesh and then washed and heated to 120℃ to remove impurities in the zeolite. Then the zeolite was activated using 1 M HCl and 1 M NaOH activators and calcined at 500 ℃ for 4 hours. This research was carried out by varying the mass of the adsorbent as much as 0.5 and 1 g and the adsorption stirring time for 30 and 60 minutes. The results show that the maximum adsorption capacity was 181.84 mg/g with an efficiency of 91% for methyl violet adsorption and 198.7 mg/g with an efficiency of 99.57% for lead adsorption. The adsorption of natural zeolite on methyl violet and lead metal followed the Langmuir isotherm pattern with adsorption capacity of 23.04 mg/g and 87.72 mg/g, respectively.